The Lemmatization of Copulatives in Northern Sotho - Prinsloo, D.J. (Lexikos, 2002)
Abstract: For learners of Northern Sotho as a second or even foreign language, the copulative system is probably the most complicated grammatical system to master. The encoding needs of such learners, i.e. to find enough information in dictionaries in order to actively use copulatives in speech and writing, are poorly served in currently available dictionaries. The aim of this article is to offer solutions to the lemmatization problems regarding copulatives in Northern Sotho and to propose guiding entries for paper and electronic dictionaries which could serve as models for future dictionaries. It will be illustrated that the maximum utilisation of macrostructural and microstructural strategies as well as the mediostructure is called for in order to reach this objective. Prerequisites will be to reconstruct the entire copulative system in a user-friendly way, to abstract the rules governing the use of copulatives and to isolate the appropriate lemmas. The treatment of copulatives in Northern Sotho dictionaries will also be critically evaluated, especially in terms of frequency of use and target users' needs.Keywords: LEXICOGRAPHY, LEMMATIZATION, COPULATIVES, INFORMATION RETRIEVAL, ACCESS STRUCTURE, ELECTRONIC DICTIONARY, MACROSTRUCTURE, MICROSTRUCTURE, CROSS-REFERENCING, MEDIOSTRUCTURE, DICTIONARY, AFRICAN LANGUAGESOpsomming: Die lemmatisering van kopulatiewe in Noord-Sotho. Vir aanleerders van Noord-Sotho as tweede of vreemde taal is die kopulatief waarskynlik die mees komplekse grammatiese sisteem om te bemeester. Die enkoderende behoeftes van sulke aanleerders, dit is om genoegsame inligting in woordeboeke te verkry ten einde kopulatiewe in spraak en skrif aktief te kan gebruik, word nie bevredig in beskikbare woordeboeke nie. Die doel van hierdie artikel is om oplossings aan die hand te doen vir die lemmatiseringsprobleme ten opsigte van kopulatiewe in Noord-Sotho en om gidsinskrywings voor te hou wat as modelle kan dien vir toekomstige papier en elektroniese woordeboeke. Daar sal aangetoon word dat maksimale benutting van makrostrukturele en mikrostrukturele strategie? asook die mediostruktuur 'n vereiste is vir bereiking van hierdie doelwit. 'n Voorvereiste is dat die struktuur van die totale kopulatiewe sisteem op gebruikersvriendelike wyse voorgestel moet word. Die re?ls wat die gebruik van die kopulatief bepaal kan dan geabstraheer word. Daarna moet die toepaslike lemmas ge?dentifiseer word. Die bewerking van kopulatiewe in Noord-Sothowoordeboeke sal ook krities ge?valueer word, veral in terme van gebruiksfrekwensie en gebruikersbehoeftes.Sleutelwoorde: LEKSIKOGRAFIE, LEMMATISERING, KOPULATIEWE, INLIGTINGSONTSLUITING, TOEGANGSTRUKTUUR, ELEKTRONIESE WOORDEBOEK, MAKROSTRUKTUUR, MIKROSTRUKTUUR, KRUISVERWYSING, MEDIOSTRUKTUUR, WOORDEBOEK, AFRIKATALE